THE ROLE OF GENE POLYMORPHISM IN THE DEVELOPMENT OF JUVENILE IDIOPATHIC ARTHRITIS IN CHILDREN (British Journal of Global Ecology and Sustainable Development, 2024)
The article describes the clinical and laboratory features of juvenile idiopathic arthritis and the consequences of the disease after treatment with chronotherapy. Clinical features of the disease, laboratory analysis results are important when choosing an effective treatment method. An effective treatment method is characterized by a faster onset of remission, prolongation of its duration and reduction of side effects of drug treatment.